2015
DOI: 10.3906/zoo-1312-54
|View full text |Cite
|
Sign up to set email alerts
|

The zooplankton composition of Lake Ladik (Samsun, Turkey)

Abstract: doi:10.3906/zoo-1312-5

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
10
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 17 publications
(11 citation statements)
references
References 18 publications
0
10
0
Order By: Relevance
“…This situation can be attributed to prey selection. Besides, Apaydin Yagci et al (2015) reported that this lake was defined as eutrophic. In this study, animal prey items such as Bosmina, Chironomid larvae, Cyclopoid copepods and Chydorus were found as the most important food types in diet.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…This situation can be attributed to prey selection. Besides, Apaydin Yagci et al (2015) reported that this lake was defined as eutrophic. In this study, animal prey items such as Bosmina, Chironomid larvae, Cyclopoid copepods and Chydorus were found as the most important food types in diet.…”
Section: Discussionmentioning
confidence: 99%
“…Apaydin Yagci et al (2015) investigated the zooplankton composition of Lake Lad ik between November 2009 and October 2010. According to their finding Rotifera was the most dominant zooplankton group in this lake (59%).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The species appear to contain typical tropical as well as cosmopolitan and littoral inhabiting (Ryding and Rast 1989). They were widespread in Turkey and worldwide because they were found almost all regions of Turkey (Güher 2000;Alper et al 2007;Dirican and Musul 2008;Bozkurt et al 2009;Saler and İpek 2009;Yıldız et al 2010;Günsel and (Emir) Akbulut 2012;Kaya et al 2012;Apaydın Yağcı 2013;Güher 2014;Saler and Alış 2014;Apaydın Yağcı et al 2015;Güher and Çolak 2015;Ustaoğlu 2015;Gürel and Saler 2015).…”
Section: Discussionmentioning
confidence: 99%
“…The study area is one of the few lakes containing floating islands in the world and it is a natural protected area owing to floating islands (Bulut, 2012;Polat, Yazıcıoğlu, Saygın, Yılmaz, & Zengin, 2015). The lake has been classified as an eutrophic and shallow lake (Apaydin Yagci, Yilmaz, Yazicioglu, & Polat, 2015). The lake's fish species are: common bream (Abramis brama), anatolian khramulya (Capoeta tinca), white bream (Blicca bjoerkna), king nase fish (Chondrostoma regium), European chub (Squalius cephalus), rudd (Scardinius erythrophthalmus), pike (Esox lucius), European perch (Perca fluviatilis), paphlagonian loach (Barbatula kosswigi) and Prussian carp (Carassius gibelio) (Uğurlu, Polat, & Kandemir, 2009;.…”
Section: Study Areamentioning
confidence: 99%